2019
DOI: 10.15171/ijer.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Physical Health: Racial Differences

Abstract: Background and aims: As suggested by the Minorities’ Diminished Return Theory, the association between socioeconomic status and health is weaker for racial and ethnic minorities compared to Whites. The current study compared Blacks and Whites in terms of the association between marital status and physical health. Methods: The State of the State Survey (SOSS) included 881 adults (92 Blacks and 782 Whites) generalizable to the state of Michigan, the United States. The marital status and self-rated physical healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Prior studies found an interaction between race and marital status (Assari & Bazargan, 2019) and race and education (Vable et al, 2019). Among Blacks and Latinos, better educational quality was associated with lower obesity, higher rates of stroke, heart disease, and smoking (a poor self-care maintenance behavior) (Vable et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies found an interaction between race and marital status (Assari & Bazargan, 2019) and race and education (Vable et al, 2019). Among Blacks and Latinos, better educational quality was associated with lower obesity, higher rates of stroke, heart disease, and smoking (a poor self-care maintenance behavior) (Vable et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…BŞBÖ tıbbı durum alt boyut puanlarında, yaş ve evli olmamanın artışa neden oldukları bulundu. Genel toplum örnekleminde yapılan birçok çalışmada da evli olmanın diğer medeni durumlara göre genel olarak daha iyi sağlık düzeyleriyle ilişkili olduğu belirtilmektedir (55,56). Yapılan bir meta-analiz çalışmasında ise yine benzer şekilde, evli bireylere kıyasla evli olmayanlarda fiziksel kırılganlık riskinin yaklaşık iki kat olduğu bildirilmiştir (57).…”
Section: Discussionunclassified
“…Additionally, various factors have been identified that can cushion the negative effects of distress on individuals, as well as their SPH, including partner support, recreational activities, relationships with colleagues/colleagues and rest periods (vacations) (McCann et al, 2013). Studies in physicians of various specialties conclude that those who have never been married and, in particular, divorced persons have significantly higher self-assessed odds of ill health than the married/cohabiting group (Amoafo, Hanbali, Patel, & Singh, 2015;Assari & Bazargan, 2019;Daily, 2019;Lindström, 2009).…”
Section: Discussionmentioning
confidence: 99%